FACTORS RELATED TO THE RISK OF HOSPITAL MALNUTRITION ON PEDIATRIC PATIENTS AT RSUP DR. M. DJAMIL PADANG IN 2020 - Jasman, Putri Elica; Masnadi, Nice Rachmawati; Pertiwi, Dian; Semiarty, Rima; Anggrainy, Fenty; Mariko, Rinang (SINERGI : Jurnal Riset Ilmiah, 2025)
Hospital malnutrition (HM) is malnutrition happened during hospitalization and has an impact on patient complications and mortality. This study aims to determine the factors associated with the risk of HM in pediatric patients at RSUP Dr. M. Djamil Padang in 2020. This study was an analytical research with the cross-sectional approach. The research was conducted at RSUP Dr. M. Djamil Padang Medical Records Section between February 2020 and December 2022. The data used is secondary data from the medical records. Bivariate analysis was conducted using the Chi- square test and Fisher's exact test. Logistic regression test was used for multivariate analysis. Statistical significance is determined if the p value <0.05. This research result showed that most of the patients were found in the age group <5 years and the main disease are lung disease. The risk factors for HM are STRONGkids scores, nutritional status, and length of stay. The prevalence of HM is 21.2%. The results of bivariate analysis showed multiple diagnoses (p=0.328), STRONGkids score (p=0.001), nutritional status (p=0.012), type of nutritional therapy (p=0.123), length of stay (p=0.001), and history of critical illness (p=0.607). The results of the multivariate analysis test showed a STRONGkids score (OR=0.143) and length of stay (OR=0.222). According to the study’s findings, STRONGkids score and length of stay are the dominant factors associated with HM in children.